Evaluasi SMKN Unggul Terpadu Anak Tuha Provinsi Lampung - Ridwan Saifuddin; Elip Heldan; Zainal Mutaqim; Ika Tri Wulan (Balitbangda Provinsi Lampung, 2018)
The policy of the establishment of SMKN Unggul Terpadu by the Provincial Government of Lampung is a form of commitment to education development in the region. This policy needs to be followed up properly, so that the initial purpose of establishing the vocational school can be realized. Evaluation is done to know the existing condition, learning process, and educational process achievement in school. This study was conducted with qualitative approach with descriptive method. Evaluation results indicate Provincial Governments need to strengthen human resource policies, especially the provision of qualified teachers and education personnel; selection and appointment of school principals; strengthening school management by optimizing the Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME); arrangement of financial management; support of practical facilities and laboratories; and encourage the splitting of land status that is still integrated with BPPT.